Zinc finger transcription factor ecotropic viral integration site 1 is induced by all-trans retinoic acid (ATRA) and acts as a dual modulator of the ATRA response - Bingemann, Sonja C (Blackwell Publishing Ltd, 2009)
Ecotropic viral integration site 1 (EVI1) plays important roles in leukaemia and development, and its expression is temporally and spatially highly restricted during the latter process. Nevertheless, the only physiological agent that to date has been shown to regulate transcription of this gene in mammalian cells is all-trans retinoic acid. Here we describe the identification of a retinoic acid response element that was located in the most distal of several alternative first exons of the human EVI1 gene and was constitutively bound by canonical retinoid receptors in NTERA-2 teratocarcinoma cells. Furthermore, it was the target of negative feedback by EVI1 on the induction of its own promoter by retinoic acid. This process required a previously described transcription repression domain of EVI1. Extending its role as a modulator of the retinoic acid response, EVI1 had the opposite effect on the RARβ retinoic acid response element, whose induction by all-trans retinoic acid it enhanced through a mechanism that involved almost all of its known functional domains. Augmentation of the retinoic acid response by EVI1 was also observed for the endogenous RARβ gene. Thus, we have established EVI1 as a novel type of modulator of the retinoic acid response, which can both enhance and repress induction by this agent in a promoter-specific manner.